ASSESSMENT OF WATER QUALITY IN THE EUPHERTES RIVER, SOUTHERN IRAQ - &et al., Abdullah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was carried out on Euphrates River, which is one of the main sources of water in Iraq to assess the water quality of Southeast of DhiQar province. Water samples were collected monthly and seasonally at three stations from October 2016 to September 2017. Eight parameters were analyzed, water temperature, dissolved oxygen, total hardness, total dissolved solid, hydrogen ion, turbidity, chloride and electrical conductivity. Monthly variations of water quality index were differing among months in three stations of study area in Euphrates River. The lowest value of WQI in station 1 was poor (1.32) in June, and the highest (2.30) in November, the value was indicated a good water. At station 2, WQI values ranged from 1.28 in August to 2.15 in February as good. The lowest of WQI (1.29) in June and the highest (1.58) in February was recorded at station 3. The ANOVA for water quality index was found statically significant (F= 0.008, P<0.05) of three stations and showed statistically significant seasonal variations of water quality index among study stations.